Requirement of New, Effective Educational Programs – Necessity for Future Development of Society - Kováčik, Peter (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
The article analyses demands of new concepts of student education on the level of secondary schools with technical focus. It urges the necessity to create new educational programs that prepare new future technical operators towards requirements of the labour market in future years in harmony with specifications of Industry 4.0. Many of job specializations is possible, at present time, to estimate only as a frame, but considering a length of study it is necessary to realize predictions at sphere of education needs consistently, expertly and continuously to introduce their results into innovations of existing educational programs or to introduce completely new, perspective educational programs by needs rising at production sector.